Roles of Trypanothione S-Transferase and Tryparedoxin Peroxidase in Resistance to Antimonials - Wyllie, Susan (American Society for Microbiology (ASM), 2008)
The clinical value of antimonial drugs, the mainstay therapy for leishmaniasis, is now threatened by the emergence of acquired drug resistance, and a comprehensive understanding of the underlying mechanisms is required. Using the model organism Leishmania tarentolae, we have examined the role of trypanothione S-transferase (TST) in trivalent antimony [Sb(III)] resistance. TST has S-transferase activity with substrates such as chlorodinitrobenzene as well as peroxidase activity with alkyl and aryl hydroperoxides but not with hydrogen peroxide. Although S-transferase activity and TST protein levels were unchanged in Sb(III)-sensitive and -resistant lines, rates of metabolism of hydrogen peroxide, t-butyl hydroperoxide, and cumene hydroperoxide were significantly increased. Elevated peroxidase activities were shown to be both trypanothione and tryparedoxin dependent and were associated with the overexpression of classical tryparedoxin peroxidase (TryP) in the cytosol of L. tarentolae. The role of TryP in Sb(III) resistance was verified by overexpression of the recombinant Leishmania major protein in Sb(III)-sensitive promastigotes. An approximate twofold increase in the level of TryP activity in this transgenic cell line was accompanied by a significant decrease in sensitivity to Sb(III) (twofold; P < 0.001). Overexpression of an enzymatically inactive TryP failed to result in Sb(III) resistance. This indicates that TryP-dependent resistance is not due to sequestration of Sb(III) and suggests that enhanced antioxidant defenses may well be a key feature of mechanisms of clinical resistance to antimonial drugs.